Early protective effect of ischemic preconditioning on small intestinal graft in rats - Wang, Shu-Feng (World J Gastroenterol, 2003)
AIM: To investigate the early protective effect of ischemic preconditioning on small intestinal graft in rats. METHODS: SD rats were randomly divided into the following groups: sham operation group (S group, n = 6), small bowel transplantation group (SBT group, n = 12), ischemic preconditioning plus small bowel transplantation group (ISBT group, n = 12). Heterotopic SBT was performed with a technique modified from that described by Monchik et al When the graft was revascularized successfully and reperfused for 1 h, samples were obtained from the different groups. Laminin was analyzed with immunohistochemical staining. Quantitative analysis of laminin positive signals was performed using image acquiring analysis system. Apoptotic epithelia of small intestinal graft were detected by the TdT-mediated dUTP nick end labeling method. The morphological change of epithelial basement membrane was observed by transmission electron microscopy. RESULTS: The mean optical density value of laminin positive signals was 39.52 ± 2.60, 13.53 ± 0.44, 25.40 ± 1.79, respectively, in S, SBT and ISBT groups. The average optical density value of laminin positive products in SBT group was sharply lower than that in S group (P < 0.05). However, the mean optical density value of laminin positive products in ISBT group was significantly higher than that in SBT group (P < 0.05). The apoptotic index (AI) in S, SBT and ISBT group was 2.2 ± 0.83,30.8 ± 3.2, 13.2 ± 2.86, respectively. The AI in SBT group was significantly higher than that in S group (P < 0.05), and AI in ISBT group was sharply lower than that in SBT group (P < 0.05). On transmission electron microscopy, the epithelial basement membrane in S group stayed normal, but in SBT group it became disrupted and collapsed, even disappeared. The lesion of epithelial basement membrane in ISBT group was slighter compared with that in SBT group. CONCLUSION: Ischemic preconditioning has an early protective effect on epithelial cells and extracellur matrix of small intestinal graft. Inhibition of epithelial cell apoptosis may be one of the mechanisms of ischemic preconditioning.